Pengembangan Metode Pengujian Kuat Tekan dan Modulus Elastisitas Pada Campuran Aspal - Edi Yusuf Adiman; Tommy Iduwin; Arief Setiawan (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This research is a development of testing methods for compressive strength and elastic modulus in asphalt mixture. The test used is the Unconfined Compressive Strength (UCS) method. The test specimens shall be cylinders 3.0 inches in diameter and 6.0 inches in height. The asphalt mixture used is the AC-WC. The asphalt content was obtained based on the optimum asphalt content, which was 5.56%. The test results showed that the compressive strength of the AC-WC ranges 5.81 MPa - 6.26 MPa, and then the elastic modulus ranges 899 MPa - 1,295 MPa. For good test results, it is necessary to pay attention to the temperature test and the flatness of the specimen’s surface.